Luna – 25 robotic arm: Results of experiment with analog of lunar regolith in lunar like conditions. (November 2022) - Litvak, M.; Kozlova, T.; Ilyin, A.; Kiselev, A.; Kozyrev, A.; Mitrofanov, I.; Tretyakov, V.; Yakovlev, V.
Abstract: The lunar lander developed by Russia for the first near polar mission Luna – 25 is equipped with a compact and multifunctional robotic arm (Lunar Manipulator Complex, LMC) designed for contact operations with the lunar regolith. The robotic arm shall excavate the lunar regolith down to tens of centimeters, collect regolith samples and deliver them to a laser ionization mass spectrometer for the elemental and isotopic composition analysis. Luna – 25 enters the final preparation stage to be ready for the launch in 2022. As a part of this activity special robotic arm ground tests were successfully conducted at Earth facilities imitating lunar like conditions. It was tested how the robotic arm could excavate the analog of lunar regolith mixed with different concentrations of water and frozen to the cryogenic temperatures (−100 °C). It was shown that mechanical strength of the frozen analog of the lunar regolith significantly increases with the increase of water ice concentration and demonstrated that the robotic arm is capable of excavating trenches and collecting samples in the ice rich analog of the lunar regolith homogeneously mixed with 1.5 wt % of water ice. Highlights: The experiment with Luna-25 robotic arm was conducted in lunar like conditions. The excavation of frozen lunar soil simulant depends on its water content. The mechanical strength of icy lunar soil simulant increases by several times. Luna-25 robotic arm is capable to collect soil sample in icy lunar regolith.